A vision of parliamentary immunity today - Limaylla Torres, Abraham de Jesús (2019)
For the lifting of parliamentary immunity in our country, the prior authorization of Congress is needed, with the initial opinion of the Commission for the Lifting of Parliamentary Immunity, which is considered a requirement for the congressman to be criminally prosecuted. The congressman has these prerogatives to carry out his functions without interference, mainly from the Executive Power, except in cases of flagrante delicto; However, with the guarantee granted by the Constitution to congressmen, other rights, effective jurisdictional protection and a reasonable term would also be affected.